The role of teachers' socio-emotional competence in reducing burnout through increased work engagement - Ornaghi, Veronica; Conte, Elisabetta; Cavioni, Valeria; Farina, Eleonora; Pepe, Alessandro (Frontiers in Psychology, 2023)
Research has highlighted the relevance of socio-emotional competence in buffering the harmful impacts of perceived stress on the psychological facets of the teaching profession. The purpose of this paper is to innovatively investigate the relationships between perceived stress, work engagement and burnout in a single comprehensive model, when considering the potential role that socio-emotional competence plays in mitigating the adverse impact of perceived stress on burnout. A total of 276 Italian in-service teachers (mean age = 46.6 ± 9.9 years) completed quantitative self-report measures of perceived stress, socio-emotional competence, work engagement and burnout. Data were analyzed by using a structural equation modeling (SEM) approach. All fit indexes supported the model’s full acceptance and suggested that teachers’ socio-emotional competence reduced the effect of perceived stress on burnout by impacting their level of work engagement. The implications of the findings are discussed in terms of promoting interventions that enhance teachers’ socio-emotional competence in order to maintain a good level of work engagement and reduce the effect of stress on burnout.